Case Report: CD19 CAR-T cells derived from recipient of umbilical cord blood transplantation effectively treated relapsed acute lymphoblastic leukemia after UCBT - Li, Hua; Li, Xiaofan; Xian, Na; Huang, Gangxiong; Li, Nainong (Frontiers in Immunology, 2025)
Recent advances in chimeric antigen receptors have provided an alternative approach for treating relapsed acute lymphocyte leukemia after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, relapsed patients who had undergone allogeneic umbilical cord blood transplantation (UCBT) have no chance of having CAR-T cells derived from donors due to lacking UCB. We present a case of a patient with Ph+ ALL who relapsed after UCBT and achieved complete morphological and molecular remission following treatment with CD19 CAR-T cells derived from the recipient post-UCBT. The patient had only grade I CRS. GVHD or neurotoxicity was not observed. More than 6 years after CAR-T cell infusion, the patient was still in hematologic and molecular complete remission with negative minimal residual disease (MRD). This case is the first to show a new strategy of practicality, efficacy, and safety of CD19 CAR-T cells derived from UCBT recipients for treating relapsed ALL after UCBT.